2020
DOI: 10.3390/life10090210
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genes Related to Oxidative Stress with the Extent of Coronary Atherosclerosis

Abstract: Oxidative stress is believed to play a critical role in atherosclerosis initiation and progression. In line with this, in a group of 1099 subjects, we determined eight single nucleotide polymorphisms (SNPs) related to oxidative stress (PON1 c.575A>G, MPO c.−463G>A, SOD2 c.47T>C, GCLM c.−590C>T, NOS3 c.894G>T, NOS3 c.−786T>C, CYBA c.214C>T, and CYBA c.−932A>G) and assessed the extent of atherosclerosis in coronary arteries based on Gensini score. An increased risk of having a Gensini sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…In the initiation and progression of atherosclerosis, oxidative stress plays a critical role [ 41 ]. Nrf-2 is a transcription factor related to antioxidant stress that increases endogenous antioxidant activity, reducing oxidative stress in the body [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the initiation and progression of atherosclerosis, oxidative stress plays a critical role [ 41 ]. Nrf-2 is a transcription factor related to antioxidant stress that increases endogenous antioxidant activity, reducing oxidative stress in the body [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health-related data from 1905 patients referred for diagnostic coronary angiography to the First Department of Cardiology of the Medical University of Gdansk between 2003 and 2006 were used to compile a study population (Wirtwein et al 2017;Wirtwein et al 2018). In this project, as in our previous publication (Racis et al 2020b), the same group with coronary atherosclerosis confirmed in coronary angiography was enrolled; however, the final analysis was conducted on 1020 individuals since 79 patients lacked follow-up data; detailed inclusion and exclusion criteria are presented in Fig. 1.…”
Section: Study Populationmentioning
confidence: 99%
“…Selection criteria included the following: (1) SNP has been described as functional in previous studies, and ( 2 S1. The risk alleles were defined according to their potential to increase the extent of atherosclerosis, as presented in our previous publication (Racis et al 2020b). After each SNP was investigated individually, the additive effect of the eight SNPs was analysed as a GRS that reflected the total impact of genetic variants.…”
Section: Genetic Risk Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Наявність поліморфного варіанта rs4880 SOD2 С47Т, при якому відбувається амінокислотна заміна Ala16Val, змінює структуру ферменту, зменшуючи ефективність його надходження в мітохондріальний матрикс, і, отже, зменшує вироблення H 2 O 2 . Проте наявні дані ролі поліморфізму rs4880 SOD2 у формуванні ризику розвитку серцево-судинних захворювань суперечливі: деякі автори стверджують, що алель ризику С, інші -що генотип ТТ збільшує ризик, проте є й дослідження, у яких не було виявлено жодних асоціацій [13][14][15]. Доступна інформація стосовно впливу поліморфізму SOD2 на формування патологічних змін при АГ досить обмежена, а при СГ і навіть маніфестному гіпотиреозі взагалі відсутня, хоча є багато даних щодо ролі rs4880 SOD2 на розвиток та перебіг злоякісних новоутворень щитоподібної залози [16].…”
unclassified